Building resilient societies after COVID-19: the case for investing in maternal, neonatal, and child health. (November 2020) - Jacob, Chandni Maria; Briana, Despina D; Di Renzo, Gian Carlo; Modi, Neena; Bustreo, Flavia; Conti, Gabriella; Malamitsi-Puchner, Ariadne; Hanson, Mark
Summary: Resilient societies respond rapidly and effectively to health challenges and the associated economic consequences, and adapt to be more responsive to future challenges. Although it is only possible to recognise resilience retrospectively, the COVID-19 pandemic has occurred at a point in human history when, uniquely, sufficient knowledge is available on the early-life determinants of health to indicate clearly that a focus on maternal, neonatal, and child health (MNCH) will promote later resilience. This knowledge offers an unprecedented opportunity to disrupt entrenched strategies and to reinvest in MNCH in the post-COVID-19 so-called new normal. Furthermore, analysis of the short-term, medium-term, and longer-term consequences of previous socioeconomic shocks provides important insights into those domains of MNCH, such as neurocognitive development and nutrition, for which investment will generate the greatest benefit. Such considerations apply to high-income countries (HICs) and low-income and middle-income countries (LMICs). However, implementing appropriate policies in the post-COVID-19 recovery period will be challenging and requires political commitment and public engagement.